Personal development of junior students from deprivation of sensory systems in special boarding school - Демчук Світлана Петрівна (Svetlana Demchuk) (Slobozhanskyi Herald of Science and Sport, 2015)
Purpose: to identify ways and content of personal development of younger pupils with sensory deprivation in the process of adaptive physical education (APE) special school. Material and Methods: with the help of the analysis and synthesis of the literature was opened the content of the personal development of younger pupils with sensory deprivation systems. Results: defines the purpose and components of personality formation and primary school children, ways for effective student-centered approach to raising a child with special needs and abilities. Conclusions: outlines ways to implement the goals and objectives of personal-centered approach in the process of adaptive physical education in the primary school children with sensory deprivation in special boarding school.